2021
DOI: 10.1590/0034-7167-2020-0759
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the contamination time by Escherichia coli on biofilm formation in surgical instruments

Abstract: Objectives: to evaluate the microbial load and adherence of Escherichia coli in different areas of the surgical instrument surface exposed to experimental contamination over time. Methods: experimental study in which fragments of crile forceps (serrated, rod and rack) were contaminated by immersion in Tryptic Soy Broth, containing 106 CFU/mL of E. coli, for 1, 2, 4, 6, 8, 12 and 24 hours. Microbial load and bacterial adherence were evaluated using microbiological culture and scanning electron microscopy, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(49 reference statements)
0
1
0
Order By: Relevance
“… 17 , 18 Furthermore, the sterilization and reuse of surgical instruments can lead to biofilm formation that is associated with device-related infection. 19 , 20 It has been reported that the structure of shark skin protects against external stimuli and reduces mechanical wear. 12 Furthermore, the structure of shark skin can prevent the attachment of bacteria and reduce biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Furthermore, the sterilization and reuse of surgical instruments can lead to biofilm formation that is associated with device-related infection. 19 , 20 It has been reported that the structure of shark skin protects against external stimuli and reduces mechanical wear. 12 Furthermore, the structure of shark skin can prevent the attachment of bacteria and reduce biofilm formation.…”
Section: Discussionmentioning
confidence: 99%